Experimental Research on a Regenerative Evaporative Cooling System - Liu Junqi; Ge Tianshu; Dai Yanjun; Wang Ruzhu (Zhileng xuebao, 2019)
Regenerative evaporative cooling is one of the main forms of dew point evaporative cooling. Regenerative evaporative cooling can cool the air below the wet bulb temperature without changing the humidity of air. An experimental system is established in this study, and an experimental research on the cooling capacity of regenerative evaporative cooling under different environmental conditions is carried out. The effects of fresh air temperature, humidity, speed, and water supply temperature on the system performance are analyzed. The experimental results show that the system provides a good cooling effect under the conditions of high temperature and low humidity. At an ambient temperature of 31 ℃, the temperature drop is 5.6 ℃ at a relative humidity of 31.5%, whereas the temperature drop is only 3.4 ℃ at a relative humidity of 60%. Reducing the temperature of the water supply can improve the cooling efficiency of the system. By setting the fresh air temperature at 35 ℃ and ?the relative humidity at 60%, the temperature drop between the inlet and outlet when the water temperature is 13 ℃ is 6.5 ℃. When the water temperature is 31 ℃, the temperature drop between the inlet and outlet is only 3.3 ℃.